2009
DOI: 10.2135/cropsci2008.04.0239
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation within and among Wildrye (Elymus canadensis and E. virginicus) Populations from the Southern Great Plains

Abstract: There is interest in Canada wildrye (CWR, Elymus canadensis L.) and Virginia wildrye (VWR, E. virginicus L.) for conservation and forage uses. Our objectives were to identify a set of molecular markers to assess genetic structure within and diversity among populations of CWR and VWR from the Southern Great Plains and to determine if these populations had an associated fungal endophyte. Nine CWR and five VWR populations and two barley (Hordeum vulgare L.) cultivars were genotyped using simple sequence repeat (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…A note about the Mediterranean hexaploids' genome: it is uncertain at this time if the M, and M., genomes from Festuca mairei St. Yves constitute the remaining genomie structure; however, there has been some plausible information that this might be the case (Saha et al, 2010). Endophyte presence or absence was confirmed by polymerase chain reaction as described by Saha et al (2009); however, rather than using seed, tiller bases were used. atlantigerta St. Yves tall fescue octoploids (2« = 8x = 56, GiGjGjGjMiMjMjMj).…”
Section: Materials and Methods Plant Materialsmentioning
confidence: 99%
“…A note about the Mediterranean hexaploids' genome: it is uncertain at this time if the M, and M., genomes from Festuca mairei St. Yves constitute the remaining genomie structure; however, there has been some plausible information that this might be the case (Saha et al, 2010). Endophyte presence or absence was confirmed by polymerase chain reaction as described by Saha et al (2009); however, rather than using seed, tiller bases were used. atlantigerta St. Yves tall fescue octoploids (2« = 8x = 56, GiGjGjGjMiMjMjMj).…”
Section: Materials and Methods Plant Materialsmentioning
confidence: 99%
“…Given that these Elymus spp. have diverged relatively recently and continue to experience interspecific gene flow (Saha et al ), selection may favor generalist endophytes that occupy a diversity of host genotypes (Leuchtmann and Clay , Saha et al , Sun ). While, our past work uncovered a link between vertical transmission and seven distinct endophyte alkaloid genotypes (Sneck et al ), the present study only included two of these genotypes and observed no difference in their transmission success.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling outcrossing between a pollen donor and recipient is possible in this system because Elymus anthers are relatively large and can be removed prior to stigma emergence, thereby preventing self‐pollination. We chose E. virginicus as the focal host species for within‐species crosses and the pollen recipient in inter‐specific crosses to reflect previously described patterns of inter‐specific outcrossing, which is mainly from E. canadensis pollen donors to E. virginicus recipients in populations where they co‐occur (Nelson and Tyrl , Saha et al ).…”
Section: Methodsmentioning
confidence: 99%
“…These resources have proven useful for genetic dissection of growth habit, plant height, flowering, and seed-retention traits (Kaur et al 2008;Larson et al 2006;Larson and Kellogg 2009) in that genus. Limited molecular genetic resources for Elymus have necessitated the use of molecular markers from other genera (Saha et al 2009). We previously reported the development of EST and SSR resources for both Elymus and P. spicata Mott et al 2011) and utilized those markers to accomplish the objectives of this work, which were to develop a genetic mapping population for Elymus, group molecular markers on genetic linkage groups homoeologous to wheat groups 1-7, and identify the seven St and seven H genome linkage groups.…”
Section: Introductionmentioning
confidence: 99%